Patients with diffuse uveitis and inactive toxoplasmic retinitis lesions test PCR positive for Toxoplasma gondii in their vitreous and blood - Novais, Eduardo A (Br J Ophthalmol, 2014)
BACKGROUND/AIMS: To determine if patients with inactive chorioretinitis lesions who experience chronic toxoplasmic uveitis test PCR positive for Toxoplasma in their ocular fluids. METHODS: Two patients undergoing long-term anti-toxoplasmic treatment developed chronic uveitis and vitritis. They underwent therapeutic and diagnostic pars plana vitrectomy. Patient specimens were tested for toxoplasmosis by real-time PCR and nested PCR. Patient specimens were also tested for the presence of Toxoplasma antibodies that recognise allelic peptide motifs to determine parasite serotype. RESULTS: Patients tested positive for Toxoplasma by real-time PCR at the B1 gene in the vitreous and aqueous humours of patient 1, but only the vitreous of patient 2. Patients were not parasitemic by real-time PCR in plasma and blood. During surgery, only old hyperpigmented toxoplasmic scars were observed; there was no sign of active retinitis. Multilocus PCR–DNA sequence genotyping at B1, NTS2 and SAG1 loci established that two different non-archetypal Toxoplasma strains had infected patients 1 and 2. A peptide-based serotyping ELISA confirmed the molecular findings. CONCLUSIONS: No active lesions were observed, but both patients possessed sufficient parasite DNA in their vitreous to permit genotyping. Several hypotheses to explain the persistence of the vitritis and anterior uveitis in the absence of active retinitis are discussed.